Harnessing Disruptive Technologies: Influence on Social Awareness of Government Initiatives - Shukla, Manisha; Waghmode, Manisha; Awati, Jayashree (Journal of Engineering Education Transformations, 2025)
In an age of rapid technological breakthroughs and shifting governance paradigms, the accessibility and success of government operations rely primarily on communication strategies that bridge the gap between administrative institutions and the populations they serve. Young India has higher expectations, and the government must respond by modernizing public service delivery, especially in health, education, government records, and other social benefits. Understanding the dynamics of how individuals desire to access these initiatives, as well as the factors that motivate or discourage participation, has become critical as governments throughout the world continue to implement new laws, programmes, and services to address a wide range of societal needs. The purpose of this research is to investigate the preferred mode of getting information about government initiatives. It also aims to explore the reasons that encourage and discourage the use of disruptive technology in the context of raising public awareness about government initiatives. Based on the conceptual framework, objectives and hypotheses were generated In order to ensure representation across demographics, a questionnaire was used to collect quantitative data from a representative sample of people through structured surveys for this research study. The creation of a structured questionnaire was directed by the study objectives. Inquiries concerning demographics, awareness of government initiatives, and preferred modes of getting information about government initiatives and reasons that encourage and discourage individuals through digital platforms are also included. The data was collected using simple random sampling method. Out of 107 questionnaire received, after data cleaning, 99 questionnaires were found suitable for data analysis. The study included a representative sample of people aged 21 and older from a range of demographic categories. Using SPSS Version 20, the data was examined with the objectives and hypothesis in consideration. Mean, standard deviation, and t-tests were employed to perform statistical and inferential analyses. Levene’s independent t-test was performed for the reasons encouraging individuals to learn about various government initiatives through digital platforms. Further, Levene’s independent t-test was performed on the reasons that discourage individuals from using digital platforms. The result revealed the reasons that encourage and discourage individuals from using digital platforms. Similar studies to detect futuristic disruptive technological improvements in the sphere of government initiatives may be conducted as the technology scenario unfolds in the future.